2015
DOI: 10.1016/j.cub.2015.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder: Sniffing Out a New Biomarker

Abstract: Early intervention improves prognosis in autism spectrum disorder, yet diagnosis is very difficult in preverbal children. A new study demonstrates that the automatic adjustments in sniffing patterns to pleasant and unpleasant odors may provide a window into early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For this reason, this network seems to be stable across ages. In literature, it has been reported that an early diagnosis could lead to better outcomes after the intervention (Dawson et al ., ; Small & Pelphrey, ). The main problem of getting an early diagnosis is that so far the most used assessment tools require abilities already structured in children, as the language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, this network seems to be stable across ages. In literature, it has been reported that an early diagnosis could lead to better outcomes after the intervention (Dawson et al ., ; Small & Pelphrey, ). The main problem of getting an early diagnosis is that so far the most used assessment tools require abilities already structured in children, as the language.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, recent research is focusing on investigating the presence of biological markers for the ASD conditions, which may overstep the limits imposed by diagnostic tests. Being a growing research interest the detection of these biomarkers for ASD (Small & Pelphrey, ; Wang et al ., ), continuing our research line in the future it would be very necessary to investigate the presence of ASN already in toddlers. If the ASN would be confirmed also in toddlers, it may be considered as an important indicator for the areas of interest.…”
Section: Discussionmentioning
confidence: 99%
“…ReebSutherland and Fox (2015), however, suggested that atypical eyeblink conditioning was a possible single ASD biomarker, and Jeste et al (2015) proposed that EEG patterns might be a possible biomarker for ASD. Small and Pelphrey (2015) proposed, BInnate olfactory behaviors may provide a link between early emerging sensory motor behaviors and the social deficits that characterize ASD( p. R675). Rozenkrantz et al (2015) reported that longer time sniffing an unpleasant odor was 81 % accurate in differentiating children with ASD from typically developing children, and Rozenkrantz et al (2015) and Small and Pelphrey (2015) suggested that a sniff test could serve as an effective single biomarker for ASD.…”
Section: Do Shared Features Provide Construct Validity For An Asd Spementioning
confidence: 99%
“…However, in the vast majority of cases such diagnosis is not done before of an age of 5-6 years, and this is probably due to the lack of objective markers. Earlier detection of autism can lead to better responses to interventions [5,6]. Recently there is a growing interest among clinicians and scholars to find the possibility of isolating objective biological markers for autism [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier detection of autism can lead to better responses to interventions [5,6]. Recently there is a growing interest among clinicians and scholars to find the possibility of isolating objective biological markers for autism [6,7]. The problem has been approached from different perspectives: behavioral, biochemical, neuroanatomical, neurophysiological, immunological, and even hormonal.…”
Section: Introductionmentioning
confidence: 99%